2018
DOI: 10.1186/s13071-018-2913-6
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of field-collected Phlebotomus argentipes (Diptera: Psychodidae) sand flies from Bangladesh and Nepal to different insecticides

Abstract: BackgroundThe sand fly Phlebotomus argentipes is the vector for visceral leishmaniasis (VL) in the Indian sub-continent. In Bangladesh since 2012, indoor residual spraying (IRS) was applied in VL endemic areas using deltamethrin. In Nepal, IRS was initiated in 1992 for VL vector control using lambda-cyhalothrin. Irrational use of insecticides may lead to vector resistance but very little information on this subject is available in both countries. The objective of this study was to generate information on the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 9 publications
0
16
1
Order By: Relevance
“…Field trials in Bangladesh, India and Nepal have shown high entomological efficacy of IRS with pyrethroids, alpha-cypermethrin or deltamethrin against P. argentipes [16][17][18][19]. Similarly, IRS with alpha-cypermethrin in Morocco brought about a significant reduction in the density of P. sergenti sandflies [20].…”
Section: Discussionmentioning
confidence: 99%
“…Field trials in Bangladesh, India and Nepal have shown high entomological efficacy of IRS with pyrethroids, alpha-cypermethrin or deltamethrin against P. argentipes [16][17][18][19]. Similarly, IRS with alpha-cypermethrin in Morocco brought about a significant reduction in the density of P. sergenti sandflies [20].…”
Section: Discussionmentioning
confidence: 99%
“…In 2009, bioassays conducted in four villages from Eastern Nepal revealed the presence of DDT resistance in one of the four populations of P. argentipes , as well as possible resistance to deltamethrin 0.05%, thereby providing an early sign of development of selection pressure against pyrethroids [10]. Bioassays in three districts of Eastern Nepal in 2015 and 2016, on the other hand showed susceptible vector populations at 60 min exposure to alpha-cypermethrin 0.05% and deltamethrin 0.05% [12], which is contrary to the results obtained in our study.…”
Section: Discussionmentioning
confidence: 99%
“…argentipes populations [10] provided a clue for possible cross-resistance to pyrethroids due to involvement of knockdown resistance (kdr) mutations in a common para-type voltage-gated sodium channel (vgsc) target site gene in nerve cells [11]. Early signs of pyrethroid resistance were observed in the Eastern part of Nepal and also in some Indian areas bordering the country [11,12]. Systematic monitoring of insecticide resistance is considered a key component of VL surveillance.…”
Section: Introductionmentioning
confidence: 99%
“…It later appeared that one of the batches of Miltefosine supplied by the national programme was a fake drug with no active substance [31], so we may consider that the effect of case management was minimal during that period. Similarly, no sand fly control activities were conducted by the government up to early 2012 [8, 12] since banned of DDT in 1997 [32], as the registration process of deltamethrin for sand fly control took a long time [13]. However, in 2013 the national programme distributed two pieces of LLIN to each patient who had completed VL treatment between 2009 and 2011 [8].…”
Section: Discussionmentioning
confidence: 99%